Expression of myogenes in longissimus dorsi muscle during prenatal development in commercial and local Piau pigs - Reis, Evelyze Pinheiro dos; Paixão, Débora Martins; Brustolini, Otávio José Bernardes; Silva, Fabyano Fonseca e; Silva, Walmir; Araújo, Flávio Marcos Gomes de; Salim, Anna Christina de Matos; Oliveira, Guilherme; Guimarães, Simone Eliza Facioni (Genetics and Molecular Biology, 2016)
This study used qRT-PCR to examine variation in the expression of 13 myogenes during muscle development in four prenatal periods (21, 40, 70 and 90 days post-insemination) in commercial (the three-way Duroc, Landrace and Large-White cross) and local Piau pig breeds that differ in muscle mass. There was no variation in the expression of the CHD8, EID2B, HIF1AN, IKBKB, RSPO3, SOX7 and SUFU genes at the various prenatal ages or between breeds. The MAP2K1 and RBM24 genes showed similar expression between commercial and Piau pigs but greater expression (p < 0.05) in at least one prenatal period. Pair-wise comparisons of prenatal periods in each breed showed that only the CSRP3, LEF1, MRAS and MYOG genes had higher expression (p < 0.05) in at least one prenatal period in commercial and Piau pigs. Overall, these results identified the LEF1 gene as a primary candidate to account for differences in muscle mass between the pig breeds since activation of this gene may lead to greater myoblast fusion in the commercial breed compared to Piau pigs. Such fusion could explain the different muscularity between breeds in the postnatal periods.
Keywords: Commercial line; Gene expression; Myogenesis; Pig; Piau breed